Knowledge and acceptability of COVID-19 vaccine among residents of Jos-south Local Government Area in Nigeria - Oluwatosin Ruth Ilori; Jeji F Danjuma; Roseline Olabisi Ige (Babcock University Medical Journal)
Objective:  Major efforts are being made to curtail the spread and adverse effects of the coronavirus pandemic using vaccines. Ever since vaccines have become available, there has been a global effort to attain herd immunity of at least 75% through the administration of vaccines. There is a dire need to assess the knowledge as well as the acceptability of COVID-19 vaccines among residents of Jos South Local Government. This study aims to assess the knowledge and acceptability of the COVID-19 vaccine among residents of Jos South Local Government.